Pancasila di ruang digital: Pengetahuan dan sikap mahasiswa baru MPI UIN Malang terhadap isu kebangsaan dan hoaks sebagai tantangan Sila ketiga Pancasila - Anam, Achmad Syarofil (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the extent of knowledge and attitudes of the 2025 entry-year students of the Islamic Education Management Program (MPI) at UIN Maulana Malik Ibrahim Malang toward the values of the Third Principle of Pancasila in the digital space. The primary focus is to measure the cognitive, affective, and conative aspects of respondents in facing digital disintegration challenges such as hoaxes and national issues. The research method employs a quantitative approach with data collection via Google Forms and basic statistical analysis. The results indicate that the respondents’ knowledge and attitudes fall within the Neutral to High categories. Cognitively, 71.4% of respondents understand the core of the Third Principle as respecting differences, and their attitude toward digital pluralism is highly positive, with an average score of 4.0. However, a gap was found in the implementation aspect; respondents tend to be neutral in distinguishing hoaxes (score 3.1), less proactive in promoting unity (score 3.3), and show low courage in confronting provocateurs on social media (score 3.2). This study recommends the need to strengthen critical digital literacy and civic courage to transform passive attitudes into active participation in maintaining national unity in the cyber world.